The impact of hemodiafiltration on cognitive function in patients with end-stage renal disease - Wang, Xiaoyan; Chen, Xiaohui; Tang, Yuting; Zhang, Liuping; Wang, Yue; Hou, Zhenghua; Jang, Wenhao; Yuan, Yonggui (Frontiers in Neuroscience, 2023)
Background Patients with end-stage renal disease are more likely to suffer cognitive impairment. Cognitive impairment may lead to long-term severe adverse consequences. Purpose To explore the impact of different blood purification therapy on cerebral blood flow and cognitive functions in end-stage renal disease. Materials and methods This prospective study evaluated patients with end-stage renal disease undergoing blood purification from January to March 2021. Matched healthy controls were also included. Participants performed neurocognitive measurements, including a mini-mental state examination, logical memory test-20-minutes delayed, verbal fluency test, digit span test, clock drawing test, and stroop color and word test C. In addition, we tested plasma amyloid-β protein levels, serum Fe and hemoglobin levels in blood samples. Cerebral blood flow was measured using pulsed pseudocontinuous arterial spin labeling. We analyzed and compared the correlation between cognitive function, biomarkers, and cerebral blood flow between patients and healthy subjects, as well as between patients with different treatments. Results A total of 44 patients with end-stage renal disease (mean age, 57.39 years ± 8.63) and 46 healthy controls (mean age, 56.15 years ± 6.40) were recruited. Patients receive hemodialysis three times a week, and 27 of them have been replaced hemodialysis for hemodiafiltration twice a month. The cognitive function of patients was worse than healthy controls (P < 0.05). The patients showed higher plasma concentrations of amyloid-β40, amyloid-β42, Tau, and pTau181 than healthy controls (P < 0.05). The group receiving both hemodialysis and hemodiafiltration had higher cerebral blood flow signal values in the left caudate nucleus (chuster-level P < 0.05, voxel-level P < 0.001). They also exhibited better verbal fluency function than the hemodialysis-only group (P < 0.05). Conclusion Patients with the end-stage renal disease showed widespread cognitive declines. Cerebral blood flow generally decreased in the cerebral cortex and increased in subcortical regions. The hemodiafiltration may protect verbal function by increasing cerebral blood flow in the left caudate.